Upaya Pembentukan Karakter di Masa Pandemi Melalui Pendidikan Agama Islam - Rosmania; Amar Latif; Ridwan Sauqi (ICO EDUSHA, 2020)
This paper aims to examine the role of Islamic religious education during the pandemic in shaping the characteristics of students. Islamic Religious Education (PAI) is a very important pillar of character education. Character education will develop well if it begins with instilling the spirit of diversity in children, therefore Islamic Religious Education materials during the pandemic are supportive for character education. By providing Islamic Religious Education learning, students are taught the Al- Qur'an and Hadith as a guide or life guide for them, given aqidah learning as their religious basis, taught morals to guide human behavior, are in the bad or good category, taught fiqh as a number of legal signs at the time of worship, and introduce the history of Islam as an exemplary life. Therefore, the main purpose of learning Islamic Religious Education is to shape the personality of the students who are represented in their behavior and mindset in everyday life. In addition, one of the successes of PAI learning during the pandemic is also determined by the implementation of appropriate learning methods.